Snack Attacks – Be Prepared - Glenda L. Warren (EDIS)
FCS-8865, a 2-page fact sheet by Glenda L. Warren, recommends ways to keep ready-to-eat snacks from the Fruit Group on hand to help children get the best nutrition. Published by the UF Department of Family Youth and Community Sciences, December 2008.